Various Factors Affected the Production of Pickled Chinese Jiaotou (Allium Chinense) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Chinese jiaotou is fresh during the harvesting season but perishable under the prevailing conditions of temperature and humidity as well as lack of adequate storage facilities. An alternative approach of preserving surplus Chinese jiaotou could be fermented to pickle products. Preservation of the Chinese jiaotou by lactic fermentation can eliminate the undesired taste and improve flavor of the vegetable. Therefore we explored a lactic fermentation from Chinese jiaotou by focusing on the effect of different parameters such as salt soaking concentration, sun drying time and CaCl2 soaking as pre-treatment; sugar concentration and fermentation time to physicochemical, microbial and sensory characteristics of pickled Chinese jiaotou. Experimental results revealed that 15% salt is soaking, sun drying in 6 hours, 0.4% CaCl2 soaking as pre-treatment for raw Chinese jiaotou; then 6% sugar in 21 days of fermentation was appropropriated to get a pleasant pickled Chinese jiaotou quality. Chinese jiaotou pickles are considered as one of the health supplements.Keywords: Chinese jiaotou, Pickle, Lactic fermentation, Soaking, Drying, Sugar, Salt.